Applied theatre techniques for community development and youth empowerment : a study of human-trafficking in South Africa and Nigeria - Akinola, Ogungbemi Christopher (My University, 2020)
One of the important duties of performative art is the idea of creating a sense of recognising people’s predicaments, especially those whose voices have been suppressed. This study seeks to employ Applied Theatre techniques to investigate community underdevelopment and youth under-empowerment with a view to discover why there is a prevalence of the human-trafficking plague in Africa, with South Africa and Nigeria as case study. On the assumption that this approach could possibly have a desolating effect through the way in which some community members would feel about their situations, field works in Mabopane (South Africa) and Eleyele (Nigeria) were conducted in order to examine the prevalence of the neglect of the youths of these communities as well as human-trafficking occurrences and possibilities. Through the results from field works, the study seeks to unveil possible relationships community and youth neglect share with the human- trafficking scourge in both regional leading countries, in particular, and the globalised world, in general. KEYWORDS: Applied Theatre; Human-Trafficking; South Africa; Nigeria; Community Development; Youth Empowerment.
Thesis (PhD. (English Studies)) -- University of Limpopo, 2020
Keywords: Applied theatre; Human-trafficking; South Africa; Nigeria; Community development; Youth empowerment.; Community development -- South Africa; Community development -- Nigeria; Human trafficking -- Law and legislation